(untitled) (Journal of Oriental Studies, 2024)
The Muslim Brotherhood is an international Islamist movement-organization founded in 1928 in Egypt by Hassan al-Banna (1906-1949). It is considered the world’s oldest Islamic organization. Its networking process became evident in the first few decades of its existence. In the 1940s, the Muslim Brotherhood had branches and representatives not only in various Egyptian cities and towns but also in the neighboring Middle Eastern countries. Presently, the Muslim Brotherhood operates both in countries with predominantly Arab and Muslim populations, as well as in Europe, North America, Russia, and various other countries. In academic literature, these structures are referred to as Muslim Brotherhood branches, distinguishing the Syrian, Jordanian, French, British, and other branches of the organization. The article aims to discuss the network of the Muslim Brotherhood movement-organization, using the European subnet as an example within the framework of David Hovhannisyan’s network theory, highlighting the type and structural features of the pan-European network.